Phoenician-Punic amphorae from Castro Marim, Portugal: provenance and contents of Pellicer amphora types B/C and D - Gaspar, Adam (2020)
Ânforas fenício-púnicas de Castro Marim, Portugal: origem e conteúdos dos tipos B/C e D de Pellicer O sítio arqueológico de Castelo de Castro Marim fica na parte mais elevada da Vila com o mesmo nome na costa sul de Portugal, perto da fronteira com Espanha. O local está situado no topo de uma colina 30 metros acima do nível do mar erguido numa área pantanosa entre a costa sudeste do Algarve e a foz do rio Guadiana. Várias campanhas de escavações arqueológicas revelaram ocupação durante a Idade do Ferro, período romano e Idade Média. O objetivo do estudo é avaliar a presença de dois tipos específicos de ânforas pré-romanas no sítio de Castro Marim em termos de proveniência e conteúdo. A produção e distribuição de ânforas Pellicer tipo B/C e D podem ser datadas do 5° ao 1° séculos a.C e estão relacionadas com a ocupação fenício-púnica da baía de Cadis e do vale do Baixo Guadalquivir. A análise petrográfica do material cerâmico com base na abordagem multi-analítica (principalmente XRD, XRF, petrografia e SEM-EDS) será focada em identificar as diferentes proveniências de amostras selecionadas de ânforas. Em casos relevantes, os resíduos extraídos dos materiais cerâmicos são estudados recorrendo a GC-MS para identificar o bem armazenado nas ânforas. Este trabalho discute a origem das ânforas analisadas e contextualiza-as no meio de produção e comércio de alimentos; Abstract: Phoenician-Punic amphorae from Castro Marim, Portugal: provenance and contents of Pellicer amphora types B/C and D The castle of Castro Marim archaeological site is located at the highest point of the town with the same name on the southern margin of Portugal close to the border with Spain. The site is placed in the hilltop 30 meters above sea level, elevated along a swampy area between the south eastern coast of the Algarve and the mouth of the Guadiana river. Several archaeological campaigns revealed occupation during the Iron Age, Roman period and the Middle Ages. The objective of this research is to evaluate the presence of two specific types of Pre-Roman amphorae in Castro Marim site in terms of provenance and content. Production and distribution of Pellicer type B/C and D can be dated from the 5th to the 1st centuries B.C and are related with Phoenician-Punic occupation of the Cadiz bay area and the Lower Guadalquivir valley. The Petrographic analyses of the ceramic material, based on a multianalytical approach (mainly XRD, XRF, petrography and SEM-EDS) is focused on identifying the different provenance of selected amphorae. In relevant cases, the residues extracted from the ceramic materials are studied by GS-MS, in order to identify possible past content of the amphorae. This thesis discusses the origin of the analysed amphorae, contextualizing them in their production, commerce and content.